Utilizing Meaningful Instructional Design to Enhance Elementary School Students' Learning Capabilities - Maiyatul Jannah Assingkily (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
In order to enhance each child's learning potential, teachers play a crucial part in the educational process. Consequently, it is up to the teacher to select the most effective learning technique. The purpose of this research is to ascertain how the Meaningful Instructional Design learning model can be implemented with students. This study employed a qualitative methodology using a descriptive approach. This Meaningful Instructional Design learning style has been shown through study to improve students' motivation and comprehension of learning. Students find it easier to absorb the content or concepts offered when there is a connection made between the lessons (text) and reality (context). in order to give students a genuine experience that will help them remember the lesson for a very long time. Students' interest in learning can therefore be raised by using the Meaningful Instructional Design learning approach.